2020
DOI: 10.1039/d0nr04363j
|View full text |Cite
|
Sign up to set email alerts
|

Electrically sensing Hachimoji DNA nucleotides through a hybrid graphene/h-BN nanopore

Abstract: The feasibility of synthesizing unnatural DNA/RNA has recently been demonstrated, giving rise to new perspectives and challenges in the emerging field of synthetic biology, DNA data storage, and even the...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
39
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(40 citation statements)
references
References 46 publications
(55 reference statements)
0
39
0
Order By: Relevance
“…The interaction with the pore edges predominantly dominates the residual or dwelling time of each target nucleotide. However, the drag force of the adjacent nucleotide plays a significant role in the speed of the translocation process . All the E i values for graphene and χ3 borophene pores are higher than the thermal energy at room temperature (0.026 eV), suggesting that higher temperature may not affect the geometrical configuration of targeted nucleotide when translocated through the pores.…”
Section: Resultsmentioning
confidence: 94%
See 4 more Smart Citations
“…The interaction with the pore edges predominantly dominates the residual or dwelling time of each target nucleotide. However, the drag force of the adjacent nucleotide plays a significant role in the speed of the translocation process . All the E i values for graphene and χ3 borophene pores are higher than the thermal energy at room temperature (0.026 eV), suggesting that higher temperature may not affect the geometrical configuration of targeted nucleotide when translocated through the pores.…”
Section: Resultsmentioning
confidence: 94%
“…From Figure , we observed that electronegative atoms (N and O atoms) of nucleotides are at a length less than 2.8 Å, which is considered to exhibit H-bonding . From the interaction energy ( E i ) values, ranges that are in the range of 0.40–0.45 eV/H-bond indicate that the interactions are H-bonding types of interactions . The reason behind the different interaction energy range for both the devices could be the chemistry of their pore edges.…”
Section: Resultsmentioning
confidence: 98%
See 3 more Smart Citations